Proteolysis targeting chimera (PROTAC)-driven antibody internalization of oncogenic cell surface receptors - Ezequiel J. Tolosa; Lin Yang; Jennifer Ayers-Ringler; Shinichiro Suzuki; Jayapal Reddy Mallareddy; Janet Schaefer-Klein; Mitesh Borad; Farhad Kosari; Amarnath Natarajan; Aaron S. Mansfield (Communications Biology)
Abstract Antibody-drug conjugates (ADCs) are increasingly used in clinic for multiple indications and may improve upon the activity of parental antibodies by delivering cytotoxic payloads into target cells. This activity is predicated upon internalization to release the cytotoxic payloads intracellularly. Since binding of ADCs to their cell surface targets does not guarantee their internalization, we hypothesize that proteolysis targeting chimeras (PROTACs) could improve the activity of ADCs through forced internalization. We show that PROTACs improve internalization of antibodies or their derivative antibody drug conjugates when both agents target the same oncogenic cell surface proteins (EGFR, HER2 or MET) by 1.4-1.9 fold in most models. PROTACs also significantly enhance cytotoxicity with HER2-targeting ADCs. These effects depend on dynamin and proteolysis. This application of PROTACs may impact the use of ADCs and provides a rationale to combine these agents in clinical trials.